2000
DOI: 10.1097/00005537-200007000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Tracheotomies: Changing Indications and Outcomes

Abstract: Objective/Hypothesis: To study the outcomes and complications associated with pediatric tracheotomy, as well as the changing trend in indications and out· comes since 1970. Study Design: Retrospective chart review at a major tertiary care children's hospital. Methods:On childr~n who underwent tracheotomy at Children's Hospital of the King's Daughters (Norfolk, VA) between 1988 and 1998, inpatient and outpatient records were reviewed. Of 218 tracheotomies, sufficient data were available on 204. Indications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
246
8
25

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(310 citation statements)
references
References 18 publications
31
246
8
25
Order By: Relevance
“…5 While the principal indications for tracheostomy in children have remained the same over the last 20 years, countless tendencies become apparent when descriptions of case reported that the incidence of tracheostomy has reduced in relation to the number of hospital admissions, although the absolute number of tracheostomies per year has remained unaltered. The same study, in conjunction with another recently-published study, 12 showed that patients are being tracheostomized for longer periods, perhaps because they are children chronically dependent on mechanical ventilation.…”
Section: Indicationsmentioning
confidence: 69%
See 1 more Smart Citation
“…5 While the principal indications for tracheostomy in children have remained the same over the last 20 years, countless tendencies become apparent when descriptions of case reported that the incidence of tracheostomy has reduced in relation to the number of hospital admissions, although the absolute number of tracheostomies per year has remained unaltered. The same study, in conjunction with another recently-published study, 12 showed that patients are being tracheostomized for longer periods, perhaps because they are children chronically dependent on mechanical ventilation.…”
Section: Indicationsmentioning
confidence: 69%
“…Nevertheless, it is most frequently performed on children less than 1 year old. [11][12][13][14] The increase in tracheostomies within this age group has been attributed to increases in the survival of premature newborn infants and those requiring prolonged ventilation. 4 The decision to perform a tracheostomy on a child is complex and depends on several factors, including the severity of airway obstruction, the difficulty and duration of intubation and the child's subjacent medical condition.…”
Section: Indicationsmentioning
confidence: 99%
“…Early complications, such as displacement of the tracheotomy cannula and pneumothorax, have been reported to occur at high rates ranging from 53% to 61% in various series (18,19). Owing to performing tracheotomy under general anesthesia in an operating room and due to the decreased number of emergency tracheotomies performed due to acute infection, serious early complications, such as pneumothorax and pneumomediastinum, have decreased since the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although infections have historically been the most common indication, 7 tracheos-tomies are increasingly indicated for prolonged ventilator dependence in children with chronic complex health conditions. 6,[8][9][10][11][12] However, most studies have focused on the indications for tracheostomy, the subsequent outcomes, or resource utilization. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Data are scant regarding the epidemiological risk factors for tracheostomy in CHD, and there have been no large-scale population-based studies.…”
Section: Introductionmentioning
confidence: 99%